Quantitative Magnetization Transfer Detects Renal Fibrosis in Murine Kidneys With Renal Artery Stenosis. Issue 3 (17th September 2020) - Jiang, Kai; Fang, Yiyuan; Ferguson, Christopher M.; Tang, Hui; Mishra, Prasanna K.; Macura, Slobodan I.; Lerman, Lilach O.
Abstract : Background: Renal fibrosis is a common pathway in tubulointerstitial injury and a major determinant of renal insufficiency. Collagen deposition, a key feature of renal fibrosis, may serve as an imaging biomarker to differentiate scarred from healthy kidneys. Purpose: To test the feasibility of using quantitative magnetization transfer (qMT), which assesses tissue macromolecule content, to measure renal fibrosis. Study Type: Prospective. Animal Model: Fifteen 129S1 mice were studied 4 weeks after either sham ( n = 7) or unilateral renal artery stenosis (RAS, n = 8) surgeries. Field Strength/Sequence: Magnetization transfer (MT)‐weighted images were acquired at 16.4T using an MT‐prepared fast‐low‐angle‐shot sequence. Renal B0, B1, and T1 maps were also acquired, using a dual‐echo gradient echo, an actual flip angle, and inversion recovery method, respectively. Assessment: A two‐pool model was used to estimate the bound water fraction ( f ) and other tissue imaging biomarkers. Masson's trichrome staining was subsequently performed ex vivo to evaluate renal fibrosis. Statistical Tests: Comparisons of renal parameters between sham and RAS were performed using independent samples t ‐tests. Pearson's correlation was conducted to investigate the relationship between renal fibrosis by histology and the qMT‐derived bound pool fraction f. Results: The two‐pool model provided accurate fittings of measured MT signal. The qMT‐derived f of RAS kidneys was significantly increased compared to sham in all kidney zones (renal cortex [CO], 7.6 ± 2.4% vs. 4.6 ± 0.6%; outer medulla [OM], 8.2 ± 4.2% vs. 4.2 ± 0.9%; inner medulla [IM] + P, 5.8 ± 1.6% vs. 2.9 ± 0.6%, all P  < 0.05). Measured f correlated well with histological fibrosis in all kidney zones (CO, Pearson's correlation coefficient r = 0.95; OM, r = 0.93; IM + P, r = 0.94, all P  < 0.05). Data Conclusion: The bound pool fraction f can be quantified using qMT at 16.4T in murine kidneys, increases significantly in fibrotic RAS kidneys, and correlates well with fibrosis by histology. Therefore, qMT may constitute a valuable tool for measuring renal fibrosis in RAS. Level of Evidence: 1 Technical Efficacy Stage: 3